2005
DOI: 10.22358/jafs/67041/2005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between various phases of milk flow at mechanical milking system and the somatic cell count in cow’s milk

Abstract: For the udder to remain healthy, milking period should be brief, and the optimal milk flow has to be reached as soon as possible and remain constant as long as possible. Research has shown that the lowest somatic cell count (SCC) for the Holstein cows logarithmic sec (LSCC = 3.03) were observed duration of increasing phase (dIP) = 0.3-0.6 min, and in those of the Simmental breed (LSCC=2.96) at dIP = 0.6-0.9 min. Furthermore, the prolongation of the plateau phase (dPP) of the milk flow curve have a beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Presence of long BT increases management costs and mastitis risk as a result of tissue stress and may indicate suboptimal udder pre-milking stimulation. In other species, it has been demonstrated that the reduction of BT is essential to improve udder health, longevity, and milking efficiency ( 30 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of long BT increases management costs and mastitis risk as a result of tissue stress and may indicate suboptimal udder pre-milking stimulation. In other species, it has been demonstrated that the reduction of BT is essential to improve udder health, longevity, and milking efficiency ( 30 , 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of milk flow traits is also important in connection with establishing the efficiency of milk ejection (Tančin and Bruckmaier 2001). Moreover recent studies on milk flow traits showed an association with udder health or somatic cell count (Mijic et al 2005, Tančin et al 2007. The effect of the lactation stage on milk flow traits was analysed by Sandrucci et al (2007), who noted significantly a higher average milk flow rate in Holstein dairy cows in the first half of lactation (up to 150 days in milk).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a long udder decrease phase is associated with overmilking of low-producing quarters. Subclinical cows had significantly shorter duration of plateau phase in comparison with the other cows, according to Mijic et al (2005) and Tančin et al (2007) who reported that time of plateau phase was negatively correlated with SCC. It can be useful to consider plateau phase as a parameter for selection; by prolonging this phase, milkability would improve without excessive increase of milk flow rate, which is associated with high SCC and high susceptibility to bacterial infections (Grindal & Hillerton, 1991; Gäde et al 2007).…”
Section: Discussionmentioning
confidence: 94%
“…machine characteristics, milking routine, milking interval) are probably the most important external factors affecting milk emission patterns (Rasmussen et al 1992; Bruckmaier, 2001; Tančin et al 2006; Sandrucci et al 2007). Moreover recent studies on milk flow traits showed an association with udder health or SCC (Mijic et al 2005; Sandrucci et al 2007; Tančin et al 2007). A good example of the complex interrelations existing among milk flow parameters, milking condition and equipment, and udder health is represented by the phenomenon of bimodality of milk flow curves.…”
mentioning
confidence: 98%